Contraceptive-use Behavior Among Women of Reproductive Age in Rural Indonesia: Rethinking Contraceptive-use Promotion - Hanna Silitonga; Nimas Pristiwanto Dwi Safitri; Bachtiar Rizki Nadiansyah; Tan Emanuella Veilen Madelline Willy; Novia Yolanda; Azyvati Karesna Putera; Minarni Wartiningsih; Ni Njoman Juliasih; Etha Rambung; Pieter David Adriaan Ferdinandus (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2026)
The use of contraception not only contributes to the reduction of maternal and child mortality rates but also serves as a strategic effort to control population growth. Long-term contraceptive methods (LCMs) are recognized as more effective and efficient when compared to non-LCMs. Nevertheless, data from the 2020 Indonesian Health Profile indicate that the majority of contraceptive acceptors continue to favor non-LCMs. Peniwen Village, characterized by a high population density of 462 individuals per square kilometer, represents a pertinent setting for examining contraceptive behavior. This study aimed to analyze the contraceptive behavior of women of reproductive age in Peniwen Village, along with their sociodemographic characteristics, and to determine the association between contraceptive method and variables such as age, education level, occupation, parity, knowledge of family planning, and family life cycle. This research employed an analytical observational design with a cross-sectional approach. The study involved 37 women of reproductive age who were family planning acceptors selected through total sampling. Data were collected using structured questionnaires encompassing demographic information, family planning knowledge, family stage, and contraceptive use. Descriptive statistics were applied to summarize the data, while the Chi-square test was used to assess associations between independent variables and contraceptive method. The findings revealed that 48.65% of respondents utilized LCMs, while 51.35% used non-LCMs. Bivariate analysis showed no statistically significant association between contraceptive method and age (p=0.249), education (p=0.695), occupation (p=0.392), parity (p=0.340), family planning knowledge (p=0.122), or family stage (p=0.500). These results underscore the necessity of adopting a more holistic approach that incorporates socio-cultural and religious dimensions to enhance family planning education among women of reproductive age in Peniwen village.